2017
DOI: 10.25115/ejrep.v9i24.1446
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Parental Autonomy Support in Academic Achievement of Asian and Latino American Adolescents

Abstract: Introduction. Driven by an overarching conceptual framework adapted from Self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
2
8
1
Order By: Relevance
“…Surprisingly, the fathers' AS did not significantly predict SE. This finding contradicts several Western works (e.g., Gonida & Cortina, 2014;Grolnick et al, 2014), and even some cross-cultural studies (e.g., Jiang et al, 2011;Liew et al, 2014;Liu et al, 2019) which found that autonomous parents cultivate learners' academic control and other related skills. This could be due to the cultural factor.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Surprisingly, the fathers' AS did not significantly predict SE. This finding contradicts several Western works (e.g., Gonida & Cortina, 2014;Grolnick et al, 2014), and even some cross-cultural studies (e.g., Jiang et al, 2011;Liew et al, 2014;Liu et al, 2019) which found that autonomous parents cultivate learners' academic control and other related skills. This could be due to the cultural factor.…”
Section: Discussioncontrasting
confidence: 89%
“…Highly autonomous parents are often found to raise learners with better adaptive abilities, for example, those having higher academic efficacy and/or control (e.g., Gonida & Cortina, 2014;Grolnick et al, 2014;Hwang & Jung, 2020). Similar findings were discovered with cross-cultural samples, where autonomous parents were found to promote positive homework emotions among young adolescents in China (Liu et al, 2019), the academic motivation, grades, and esteem of Asian and American high school learners (Jiang et al, 2011), and the academic grades of Chinese American high school students (Liew et al, 2014). However, these studies did not distinguish between mothers' and fathers' parenting.…”
Section: Influence Of Parental Support On Academic Efficacysupporting
confidence: 56%
See 2 more Smart Citations
“…The learning support services provided by parents significantly positively affect students' self-esteem, academic performance, and learning motivation (Jiang et al, 2011). In the case of online learning, parents' participation in students' learning is conducive to students' success (Stevens and Borup, 2015).…”
Section: Learning Support Servicesmentioning
confidence: 99%